Understanding the Impacts of Upper-Tropospheric Cold Low on Typhoon Jongdari (2018) Using Piecewise Potential Vorticity Inversion - Yan, Ziyu; Ge, Xuyang; Wang, Zhuo; Wu, Chun-Chieh; Peng, Melinda (Monthly weather review, 2021)
Typhoon Jongdari (2018) had an unusual looping path before making landfall in Japan, which posed a forecasting challenge for operational numerical models. The impacts of an upper-tropospheric cold low (UTCL) on the track and intensity of Jongdari are investigated using numerical simulations. The storm track and intensity are well simulated in the control experiment using the GFS analysis as the initial and boundary conditions. In the sensitivity experiment (RCL), the UTCL is removed from the initial-condition fields using the piecewise potential vorticity inversion (PPVI), and both the track and intensity of Jongdari change substantially. The diagnosis of potential vorticity tendency suggests that horizontal advection is the primary contributor for storm motion. Flow decomposition using the PPVI further demonstrates that the steering flow is strongly affected by the UTCL, and the looping path of Jongdari results from the Fujiwhara interaction between the typhoon and UTCL. Jongdari first intensifies and then weakens in the control experiment, consistent with the observation. In contrast, it undergoes a gradual intensification in the RCL experiment. The UTCL contributes to the intensification of Jongdari at the early stage by enhancing the eddy flux convergence of angular momentum and reducing inertial stability, and it contributes to the storm weakening via enhanced vertical wind shear at the later stage when moving closer to Jongdari. Different sea surface temperatures and other environmental conditions along the different storm tracks also contribute to the intensity differences between the control and the RCL experiments, indicating the indirect impacts of the UTCL on the typhoon intensity.